1996
DOI: 10.1080/016909696387079
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Monitoring

Abstract: The primary use of sequence monitoring (also known as syllable or fragment monitoring) has been to determine which linguistic units are involved in word recognition, and how these units might differ across languages. The task involves presenting subjects with targets that are either congruent or incongruent with a linguistic unit in the target-bearing item. Faster detection latencies to congruent targets are taken to indicate their perceptual relevance. For example, the finding that subjects are faster to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Nonetheless, we believe that they do not provide conclusive evidence to support such a claim. Several authors have argued that the syllable effect in fragment detection experiments may not reflect early perceptual processing (Frauenfelder & Kearns, 1996;Kolinsky, 1998) and might involve postlexical matching/decision processes (McQueen, 1998). In fact, in a reanalysis of the original data, Dupoux (1993) showed that the target/carrier interaction was only observed for slower participants.…”
Section: The Role Of the Syllable In Spoken Word Recognitionmentioning
confidence: 99%
“…Nonetheless, we believe that they do not provide conclusive evidence to support such a claim. Several authors have argued that the syllable effect in fragment detection experiments may not reflect early perceptual processing (Frauenfelder & Kearns, 1996;Kolinsky, 1998) and might involve postlexical matching/decision processes (McQueen, 1998). In fact, in a reanalysis of the original data, Dupoux (1993) showed that the target/carrier interaction was only observed for slower participants.…”
Section: The Role Of the Syllable In Spoken Word Recognitionmentioning
confidence: 99%
“…An influential finding taken to favor prelexical syllabic classification comes from a seminal study by Mehler, Dommergues, Frauenfelder, and Seguí (1981) using the sequence detection task (see Frauenfelder & Kearns, 1996, for further details). In this study, French listeners were faster at sequence detection for targets that matched the first syllable (e.g., ba in balance or bal in balcon) than for targets which corresponded either to more or less than the first syllable (BA in BALCON or BAL in BALANCE).…”
mentioning
confidence: 99%
“…Second, the sequence detection task requires listeners to explicitly segment the carrier and evaluate the match with the target (e.g., Frauenfelder & Kearns, 1996). Hence, the observed effects may not reflect early perceptual processing, but conscious segmentation strategies applying at the postrecognition level (Kolinsky, 1998;Morais, 1985;Morais, Content, Cary, Mehler, & Seguí, 1989).…”
mentioning
confidence: 99%
“…/bal/, cf. Mehler, Dommergues, Frauenfelder & Segui 1981 ;Frauenfelder & Kearns 1996), is another similar task. In this experiment, we present listeners with items ending in [ji] and others ending in [di] in order to determine whether listeners will use the information about morpheme boundaries provided by the palatalization alternation in order to decide whether a given item contains the subject particle.…”
Section: Rationalementioning
confidence: 99%